2017
DOI: 10.1631/jzus.b1600367
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activity of alcohol aqueous extracts of Crypthecodinium cohnii and Schizochytrium sp.

Abstract: Abstract:Crypthecodinium cohnii (dinoflagellate) and Schizochytrium sp. (thraustochytrid) are the main sources for docosahexaenoic acid (DHA). The present study aimed to evaluate the antioxidant activity of petroleum ether, ethyl acetate, n-butanol, and water fractions of alcohol aqueous extracts of these two microalgae and to provide a theoretical basis for comprehensive utilization. The antioxidant activity was determined by total antioxidant capacity (TAC) determination, 2,2-diphenyl-1-picrylhydrazyl (DPPH)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 42 publications
3
13
0
Order By: Relevance
“…Previous studies have shown that the antioxidant ability of oleoresin is due of its electron transfer capability, which is determined by FRAP. However, the values determined by ORAC, DPPH, and ABTS assays, designed to measure the ability to transfer hydrogen atoms to neutralize a free radical, were low compared to those reported in other studies that used natural extracts [53,54,55,56]. This mechanism of action can be explained by the presence of astaxanthin in oleoresin, which is responsible for electron transfer.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…Previous studies have shown that the antioxidant ability of oleoresin is due of its electron transfer capability, which is determined by FRAP. However, the values determined by ORAC, DPPH, and ABTS assays, designed to measure the ability to transfer hydrogen atoms to neutralize a free radical, were low compared to those reported in other studies that used natural extracts [53,54,55,56]. This mechanism of action can be explained by the presence of astaxanthin in oleoresin, which is responsible for electron transfer.…”
Section: Resultsmentioning
confidence: 70%
“…The phenolic compounds identified while determining the total phenolic content are common, and all of them exhibited antioxidant activities [48,59]. Several studies have evaluated different solvents to increase the extraction of these molecules from microalgal biomass [48,56]. Microalgal strains such as Crypthecodinium cohnii (dinoflagellate) and Schizochytrium sp.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The content of total polyphenols (TPs) and total flavonoids (TFs) was determined as described previously [15]. As for TPs, the sample volume in this test was 0.2 ml.…”
Section: Methodsmentioning
confidence: 99%
“…The main molecules identified to date in microalgae are phloroglucinol (5) and phenolic acids derived from hydroxybenzoic acid (6) and hydroxycinnamic acid (7). Several studies have also shown the presence of weak concentrations of flavonoids e.g., [8,[47][48][49][50][51][52][53][54]. All of these molecules are found in higher plants where their concentration is generally higher than in microalgae [55].…”
Section: Phenolic Compoundsmentioning
confidence: 99%